Sucrose-to-ethanol microalgae-based platform using seawater - Sanz Smachetti, María Eugenia (2020)
Microalgal biomass is increasingly considered a promising feedstock for the production of bioethanol because it has simpler biochemical composition and structural features than plant feedstocks. However, it still requires hazardous and/or expensive acid or enzymatic saccharification processes before its conversion into ethanol by fermentation. To bypass this limitation, we identified microalgal strains that accumulate up to 10% (w/w) of sucrose, a readily fermentable sugar. Conditions were optimized to produce sucrose in half-strength seawater, as well as efficient extraction by very mild procedures, and conversion into ethanol. We present a model based on cultivation in environmental photobioreactors that predicted a productivity of 4,200 L ethanol · ha-1 · year-1 in raceway ponds in Brazil, approaching the average sucrose and ethanol productivity from sugarcane.